IDEOLOGY OF KIAI IN EDUCATION AT SMAN OF DARUSSHOLAH SINGOJURUH, DISTRIC SINGOJURUH – BANYUWANGI PROVINCE OF EAST JAVA - Mursidi, Agus; Rumawan Salain, Putu; Anom Kumbara, A.A. Ngurah; Wiasti, Ni Made (E-Journal of Cultural Studies, 2019)
The implementation of education in Indonesia was mandated by the UUD 1945. The implementation was carried out at the SMAN. Education policy in schools creates controversy as a form of impact on ideology of kiai. The policy deviation is in the form of changes in school curriculum, differences in the learning process, and religion as a public high school identity. This study aims to: (1) find out the ideology of kiai in the dominance of education in SMAN (2) knowing the practice ideology of kiai in SMAN (3) knowing the meaning in the ideology of kiai at SMAN. This is a qualitative research with data obtained through interviews, observation, and document study. The results showed that (1) the dominance of kiai in education due to influence of historical factors in the establishment of SMAN, the role of school committees with most members of Islamic boarding schools, and the political role of kiai (2) Ideology of kiai practices included the formation of superior classes, curriculum changes school identity and extracurricular activities (3) the meaning contained in the ideology of kiai in education at SMAN is a conflict of interest, emancipatory education, economics, and the meaning of polarization. Keywords: Ideology, Kiai, SMAN